Flexible carbon nanotube/polyurethane electrothermal films. (December 2016) - Luo, Jie; Lu, Huifen; Zhang, Qichong; Yao, Yagang; Chen, Minghai; Li, Qingwen
Abstract: Carbon nanotube (CNT)-based composites are ideal materials for electrothermal applications because of their lightweight, excellent conductivity, heat sensitivity, and easy processability. In this study, high-performance electrothermal films were synthesized by a novel layer-by-layer method. Electrothermal films were prepared by pouring CNT solution into the designed mold and subsequent curing of thermoplastic polyurethane (TPU) applied on the CNT layer. The flexible films showed sensitive electrothermal performance, and a steady-state temperature of ∼140 °C could be reached at 10 V. In addition, temperature versus voltage and time-dependent temperature results show that the heating performance was strongly dependent on the CNT content and input power. Moreover, they can bear large deformations, which could be widely used in defogging and defrosting applications. Graphical abstract: